Il teatro come forma che pensa. Pregiudizio antiteatrale, materialità e abiezione nella scena postdrammatica (Itinera, 2013)
If one turns to the source of the so-called antitheatrical prejudice, Plato, and explores beside his notorious critics to the arts also his statements about the spectatorship, something intriguing appears. It appears that common origins link the theoretical meditation and the theatrical specta-torship, encapsulating these two occupations in the Greek word theoria, in which the sense of sight is crucial to both the act of going to the thea-tre and of engaging in theoretical inquiry. This mutual and ambivalent attraction of theatre toward philosophy and of philosophy toward theatre reaches a sort of climax in the era of post-dramatic theatre. Dismissed the general aversion to “theatricality” – still at stake within the Modern-ism theatre – contemporary theatrical scene has been demonstrating to what extent theatre is in itself a “thinking form”, or a form of thinking embodied in the material presence of the performer. Far from causing the sort of embarrassment and frustration denounced by modernist theatre artists such as Edward Gordon Craig, the actor’s deliberate vulnerability possibly enables our own and prompts us toward empathy and theoreti-cal understanding. Watching live performance is watching the actor dy-ing onstage; sharing that liveness promotes a necessary and moving con-frontation with mortality.